2018
DOI: 10.4034/pboci.2018.181.02
|View full text |Cite
|
Sign up to set email alerts
|

Milk Reverts the Effects of an Enamel Erosive but Healthy Diet

Abstract: Objective: To determine the erosive effects of popular fruits and vegetables on enamel, and the potential counter effects of milks. Material and Methods: Ten popular fruits and vegetables were individually blended in a juicer to form a fruit or vegetable juice. The labial surfaces (three for each treatment group) were then immersed for thirty minutes in a fresh juice of one of ten products: strawberry, spinach, pineapple, grapefruit, green pepper, pickle, orange, apple, tomato, and carrot. In a second experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(27 reference statements)
2
1
0
Order By: Relevance
“…Calcific deposits of various patterns were haphazardly distributed filling all cracks and surface defects. This finding was parallel to that reported by Chung et al, 2013 and Vieira et al, 2018 (39,37) . The authors proved that lactose free milk significantly raised enamel micro-hardness when compared to almond milk following treatment with Coca-Cola, suggesting remineralization of eroded enamel.…”
Section: Discussionsupporting
confidence: 92%
“…Calcific deposits of various patterns were haphazardly distributed filling all cracks and surface defects. This finding was parallel to that reported by Chung et al, 2013 and Vieira et al, 2018 (39,37) . The authors proved that lactose free milk significantly raised enamel micro-hardness when compared to almond milk following treatment with Coca-Cola, suggesting remineralization of eroded enamel.…”
Section: Discussionsupporting
confidence: 92%
“…Also, milk has bioactive peptides, casein phosphor proteins that are strongly absorbed in the surface of enamel and able to reduce the activity and adsorption of glucosyltransferase enzymes, also preventing or reducing the dissolution of the enamel (26) . The results of remineralization effect of milk are in agreement with Vieira et al (27) that concluded that whole milk showed significant higher gain of enamel microhardness of eroded enamel as compared to filtered water.…”
Section: Discussionsupporting
confidence: 90%
“…The perceived increase in erosive tooth wear and a healthier diet that can be more acidic has made us suggest the utilization of fluorides to counteract the effects of acids from the diet on the dental enamel [2]. In addition, drinking milk may be a way to minimize losses of hard tooth structure [3,4]. The mechanism underlying this effect appears to be related to an impact on bacteria adhesion to the acquired enamel pellicle when one drinks milk [5].…”
Section: Introductionmentioning
confidence: 99%